Atriplex (Atriplex halimus): Distribution, Morphology, Physiological Tolerance to Salinity and Drought: A Review - Gharibeh, Omar E.; Shiyab, Safwan M.; Saoub, Hani (International Journal of Membrane Science and Technology, 2023)
Atriplex halimus is a halophyte plant that is grown in semi-arid and arid regions due to its high capacity to grow in high salinity and drought conditions. The objective of this paper is to review the physiological and morphological changes of A. halimus under different conditions of salinity and drought conditions, as well as compare the different results that are concerned with this plant in the different areas where this plant exists. The result of this review has shown that A. halimus adapt to different saline conditions by creating the balance of the vegetative growth as well as changing the leaves physiology to adapt to the drought conditions by decreasing the water content which Na creates the osmotic adjustment. The A. halimus can reduce/or increase the photosynthesis process depending on the level of drought and salinity conditions. The accumulation of Na increased in the plant as the soil salinity increased. The review has shown that A. halimus increase the uptake of heavy metals if it has high concentrations in soil. The review results show that the different morphological and physiological changes of A. halimus differ from one area to another depending on the drought conditions and soil salinity concentrations. The results showed that A. halimus can be used to rehabilitate deserts that suffer high salinity and drought. Moreover, it can be used to treat the soil contaminated with heavy metals.